Topical 1% Voriconazole for Mixed Scedosporium and Exophiala Subcutaneous Infection in a Kidney Transplant Recipient - Olivier Paccoud; Pierre Sohier; Camille Cotteret; Sarah Guégan; Fanny Lanternier (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)